ISLAM AND TERRORISM: UNRAVELLING NARRATIVE BIASES IN AN INDONESIAN INDIE FILM - Nurmansyah, Mochamad Andhy; Ida, Rachmah; Irawanto, Budi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
Since the 9/11 attack on the World Trade Center in New York in 2001, terrorism in the name of Islam has become a common occurrence in Indonesia. As a result, violent images of Islam widely circulated in the media. Islam and its minor images have permeated the Indonesian entertainment media landscape, including independent cinema. This study addresses the lack of research on Indonesian independent films with Islamic themes. In its earliest stage, this study studied how an independent movie, Train To Heaven (TTH), examined the language surrounding terrorism in the name of Islam. The analysis in this paper, which was conducted within the context of social semiotics, indicated that the sarcastic tones used in the text were consistent with the film's principal focus, which was rejecting violent acts in the name of Islam. TTH, an independent film that tackles the issue of terrorism committed in the name of Islam, frequently expresses resistance to the act at the outset of its cinematic portrayal. As the scenes develop, the story becomes increasingly ambiguous. TTH's antagonistic stance on alleged Islamic terrorism has not been maintained. The emergence of contradictions after the story, the TTH indie film's position, which has not been fully designed to address a specific alternative